Children's rights and girl child marriages : a case study for Malawi - Mkali, Theodora Talumba (Department of Public Law, 2016)
The harmful traditional practice of child marriage remains one of the main challenges towards the full realization and enjoyment of children's rights in Africa. In the sub-Saharan Africa alone, countries such as Malawi are faced with the problem of child marriage where as high as 40% of the women are married as children. Malawi has a substantive legal framework that affords protection and prohibits the harmful practice of child marriage. However, child marriages remain prevalent in Malawi where harmonisation of the laws is problematic. This has the effect of robbing the girl child of her childhood, access education and health among other rights that she is entitled. Addressing this problem in Malawi as a matter of urgency is crucial for the promotion, protection and realisation of children's rights, especially to the girl child. This study therefore conducts an analysis of the legal framework and contextual practice of child marriage in Malawi based on desk research of various laws in Malawi and literature. This analysis is premised on the understanding that human rights law within a legal framework plays a major role towards ensuring that young girls are protected from child marriage and its attendant consequences. This study has found that the laws of Malawi are not synchronised with each other especially with the Malawi Constitution with regard to protecting the rights. The case in point for instance is the recent passing of the Marriage, Divorce and Family Relations Act which reflects international and regional human rights standards, but is inconsistent with the Constitution of Malawi. It is recommended that Malawi should through the law address the practice of child marriage by amending the Constitution to remove any ambiguities. In this regard, creating a protective legal framework must not be done in vain. This should be supported by effective implementation of national development plans that aim to realise the rights of children, especially the girl child.